2014
DOI: 10.1007/s10971-014-3443-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ag/NiO composite nanosheets and empty microspheres and their highly effective electrocatalytic properties

Abstract: Ag/NiO composite nanosheets and empty microspheres were fabricated by calcining the precursors synthesized via hydrothermal and solvothermal procedures involved four methods. The as-prepared samples were characterized by thermogravimetric and differential thermal analysis, X-ray diffraction, X-ray photoelectron spectroscopy, transmission electron microscopy and field emission scanning electron microscopy, respectively. The electrocatalytic properties of Ag/NiO composites modified on a glassy carbon electrode f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In recent years, a lot of research has been done on the use of NiO in more areas and doping with metals to increase its performance further. New types of materials with very good chemical and physical properties can be synthesized by doping NiO with metal oxides 2 or other metals 41–52 . Studies are also carried out to use metal‐added materials as catalysts, due to the synergistic effect created by the use of metals such as Ag, Au, and Pt together.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a lot of research has been done on the use of NiO in more areas and doping with metals to increase its performance further. New types of materials with very good chemical and physical properties can be synthesized by doping NiO with metal oxides 2 or other metals 41–52 . Studies are also carried out to use metal‐added materials as catalysts, due to the synergistic effect created by the use of metals such as Ag, Au, and Pt together.…”
Section: Resultsmentioning
confidence: 99%
“…Studies are also carried out to use metal‐added materials as catalysts, due to the synergistic effect created by the use of metals such as Ag, Au, and Pt together. Many studies have been conducted in the literature with different sizes of NiO, 42–46 NiO/Ag, 43,47,48 NiO/Pt, 41,49,50 and NiO/Au 49,51,52 and these materials have been used in a variety of applications as electrocatalyst, 43,47,49–51 photocatalysts, 48,53,54 supercapacitors, 44,46 batteries, 45,55 adsorption, 29,51 and sensor 56–58 . When the catalytic activities of the materials are examined, it is seen that it depends on the morphology, size and composition of the structure.…”
Section: Resultsmentioning
confidence: 99%
“…It is also reported that nickel oxide nanoparticles modified electrodes exhibited high electrocatalytic activity towards different organic and bio-molecules [43]. In recent years, a great deal of progress has been made in NiO based materials for instance, NiO/CuO nanocomposites [44], Ni 0 /NiO core-shell nanostructure [45],Ag/NiO nanocomposite [46], NiOÀ CeO 2 nanocomposite [47],NiOÀ NPs-ionic liquid [48] for electrochemical sensing of pÀ NP.…”
Section: Introductionmentioning
confidence: 99%